Effects of L-carnitine on fetal growth and the insulin-like growth factor system in pigs - Waylan, A.T.; Johnson, B.J.; Kayser, J.P.; Gnad, D.P.; Dunn, J.D.; Sissom, E.K.; Higgins, James J.; Woodworth, J.C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Twelve sows were used to examine the effects of feeding L-carnitine from artificial insemination to mid-gestation on maternal circulating IGF-I and carnitine concentrations and fetal growth. Supplementing L-carnitine did not influence the serum concentration of IGF-I. However, sows that were fed carnitine had increased circulating plasma free carnitine. Litters from sows fed L-carnitine were heavier and had more fetuses. The increase in litter fetus number was not detrimental to other growth traits such as individual fetal weight or crown to rump length. Our study suggests that feeding L-carnitine to gestating sows is beneficial for fetal growth and development.
Keywords: Sows; Carnitine; Insulin-like growth factor; Swine